Impulsive Control of a Cam-Follower Oblique-Impact System. (25th May 2017) - Lu, N.; Ren, X. M.; Jiang, T. D.; Yang, Y. F.
Abstract : The transient impact hypothesis was extended, and the oblique collision model was established by considering the tangential slip. In order to solve this problem, the oblique-impact equations for cam-follower were transformed into a linear complementarity problem. Impulsive control method was employed to control or anti-control the nonlinear responses. The simulation results show that the cam-follower system performs very complex nonlinear characteristics, such as period, quasi-period and chaos responses. Using the impulsive control method, the nonlinear responses of the cam-follower system can be controlled to P ( n, n ) and P ( ∞, n ) or anti-controlled to chaos.